A democratização do ensino fundamental de 06 a 14 anos: que concepção de democracia tem sido adotada nas leis federais? - Ressineti, Telma Renata [UNESP] (2014)
This aims to discuss the democratization of the elementary school, in Brazil, for children aged 06 -14 years. We elected the period 1971 to 2006 to be two important moments in the history of Brazilian education: in 1971 occurred in Brazil approval of the law n. 5.692/71 which extended the duration of primary education from 4 to 8 years, at a time when capitalism was going through a crisis, whose solution was given by overcoming the Taylorist -Fordist organization of work, with the implementation of neoliberal policies, and in 2006, at which time the law was passed n.11.274 , extending the duration of compulsory elementary education for 09 years. Since then there have been many efforts of the government through laws, campaigns, decrees to facilitate students access, permanence and certification. Faced with this situation, we are interested in answering the question: What are the concepts of democracy and education democratization present on federal laws governing the expansion of the elementary school at the right age in state public schools in Brazil? This research was drawn up as a qualitative methodological approach and procedures like the documentary and bibliographical analysis approach. Our theoretical and methodological framework is dialectical and historical materialism, which understand the educational practice and the elements that constitute it, in order to grasp their material more fully, from the assumptions of the class struggle, not the neutrality of the state, as an enabler in the realization of social rights, especially the right to education process